Role of Kletik oil, Ginger and Garlic Extracts towards Soft Tissue Injury - Qing Nan, Benjamin Yong; Ismiarto, Yoyos Dias; Sugianli, Adhi Kristianto (Althea Medical Journal, 2016)
Background: There is an increased consumption of herbal medicines throughout the world as an alternative treatment for curing health problems. Several herbal medicines are believed to contain anti-inflammatory properties that could trigger healing process. But little is known about the combination effect of herbal medicines. Therefore, the objective of the study was to determine the effects of garlic, ginger and coconut oil (kletik oil) on soft tissue injury (swelling).Methods: The study was held in the research laboratory of Faculty of Medicine Universitas Padjadjaran, from 24th September until 1st October 2014. This experimental study used 7 healthy rabbits (Lepus curpaeums, Â±2.5kg) as animal models for each control and intervention group with induced soft tissue injury in the dorsal ear to mimic swelling (inflammation). The mixture of herbs was applied on the injured site in the trial group, while the healing process was denoted by the thickness of edema and time of observation. The data was analyzed using Wilcoxon test.Results: The study results showed that after observation time of 0.5 hour, 2 hours, and 5 hours, edema thickness was unvaried. Onset of action of the herbal mixture began 24 hours after induced injury, with significant difference of edema thickness on both groups; hence the p-value 0.019 (p<0.05).Conclusions: The herbal mixture of ginger, garlic, and coconut oil (kletik oil) contains anti-inflammatory properties to enhance the healing process of soft tissue injury. [AMJ.2016;3(3):421â4]DOI: 10.15850/amj.v3n3.870Â